Using Bloom’s taxonomy to assess social media assignments - Sylvia IV, J.J. (Journal of Interdisciplinary Studies in Education, 2019)
This paper argues that by linking social media assignments to particular levels of Bloom’s Taxonomy, instructors can more easily and straightforwardly assess assignments. Much confusion exists over how to best incorporate these tools, and further, how to properly assess student performance related to social media. Often social media is used simply as an additional and optional channel of communication, rather than as an inherent part of a graded assignment, due in part to the difficulties of assessment. Using social media effectively and collaboratively is an important aspect of literacy in the 21st century; it is therefore important to move beyond merely incorporating the tools, but also assessing the use of the tools